Where Power Lies – The Archaeology of Transforming Elite Centres in the Landscape of Medieval England c. AD 800–1200 - Gould, David; Creighton, Oliver; Chausée, Scott; Shapland, Michael; Wright, Duncan (Medieval Settlement Research, 2024)
‘Where Power Lies: The Archaeology of Transforming Elite Centres in the Landscape of Medieval England c. AD 800-1200’ was a joint project between Newcastle University, the University of Exeter and the Portable Antiquities Scheme (PAS) that answered key questions regarding the earliest medieval lordly centres. The project, which ran from November 2022 to April 2024, employed a range of archaeological, historical and geographical methodologies to map and explore sites on a range of scales, from region-wide studies to site-specific investigations. It had a particular emphasis on exploring locations where there is evidence for an aristocratic residence and contemporary church combined, as it is these places that we can best trace a wide range of elite investment over time.